(untitled) (Simbiótica. Revista Eletrônica, 2025)
The present work has as its general objective the study of the concepts and ideas developed by Erving Goffman (1922–1982) about deteriorated identity and stigma. As a specific objective we intend to analyze and study how the author – and his concepts and theories – dialogue with the state of the art of Anti—Discrimination Law. From these paradigms, we intend to identify how the removal of stigma and its forms of stigmatization promote the personal and social identities of individuals and collectives, their recognition and resistance. Thus, the science of anti—discrimination – including in law – presupposes multiple actions aimed at ensuring that discriminated minorities and stigmatized groups are protected and have their own identities based on personal, community and collective identification processes